Pion-pion cross section from proton-proton collisions at the LHC - Kopeliovich, Boris Z.; Potashnikova, I. K.; Schmidt, Iván; Pirner, Hans J.; Reygers, Klaus (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The zero-degree calorimeters (ZDC) installed in the ALICE, ATLAS and CMS experiments at the LHC make possible simultaneous detection of forward-backward leading neutrons, pp→n X n. Such data with sufficiently high statistics could be a source of information about the pion-pion total cross section at high energies, provided that the absorption corrections, which are expected to be strong, are well understood. Otherwise, making a plausible assumption about the magnitude of the pion-pion cross section, one can consider such measurements as a way to study the absorption effects, which is the main focus of the present paper. These effects introduced at the amplitude level are found to be different for the pion fluxes, which either conserve or flip the nucleon helicity. The pion fluxes from both colliding protons are essentially reduced by absorption; moreover, there is a common absorption suppression factor, which breaks down the factorized form of the cross section. We also evaluate the feed-down corrections related to the initial/final state inelastic processes possessing a rapidity gap, and found them to be small in the kinematic range under consideration. The contribution of other isovector Reggeons, spin-flip natural parity ρ and a2 and spin-nonflip unnatural parity a1, are also evaluated and found to be rather small.
Gesehen am 21.07.2020